2013
DOI: 10.11622/smedj.2013127
|View full text |Cite
|
Sign up to set email alerts
|

Management of ruptured intracranial aneurysms in the post-ISAT era: outcome of surgical clipping versus endovascular coiling in a Singapore tertiary institution

Ng Z2,
et al.

Abstract: O r i g i n a l A r tic le 332 I NTRO D U C TIO NSubarachnoid haemorrhage (SAH) secondary to intracranial aneurysm rupture remains one of the most serious neurosurgical emergencies today. Intracranial aneurysms are acquired cerebrovascular anomalies that develop throughout a patient's lifetime.(1) They are arterial lesions defined by thinned and dilated regions of the cerebrovascular wall that exhibit loss of the internal elastic lamina, thinning of the tunica media, and subsequent remodelling and degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Recently, a meta-analysis also draw the same conclusion [22]. In addition, some investigations show that surgical clipping is more prone to hydrocephalus [23], cerebral vasospasm [22,24] and epilepsy [21]. In this study, there was a difference of mean CSF S100B between high grade and low grade, which demonstrated that the brain injury degree of high grade was significantly higher than that of low grade.…”
Section: Discussionsupporting
confidence: 68%
“…Recently, a meta-analysis also draw the same conclusion [22]. In addition, some investigations show that surgical clipping is more prone to hydrocephalus [23], cerebral vasospasm [22,24] and epilepsy [21]. In this study, there was a difference of mean CSF S100B between high grade and low grade, which demonstrated that the brain injury degree of high grade was significantly higher than that of low grade.…”
Section: Discussionsupporting
confidence: 68%
“…This trial has influenced treatment of aneurysms at many centers with a trend from surgical clipping toward endovascular management. 70 72 However, with regard to treatment of pediatric aneurysms, one aspect of the International Subarachnoid Aneurysm Trial is particularly important: the long-term follow-up published in 2009 showed a small but increased risk of recurrent bleeding from a coiled aneurysm compared to a clipped aneurysm. 73 Long-term durability of treatment is crucial in children given the long remaining lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…The use of coiling spreads from primarily large, teaching hospitals to smaller, non-teaching hospitals (28). Similar trends are in Korea, Australia and Singapore (17,18,29,30).…”
Section: Discussionmentioning
confidence: 79%